2008
DOI: 10.1051/forest:2008039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of site on fibre, kraft pulp and handsheet properties of Eucalyptus globulus

Abstract: -• Eight-year old trees from two Eucalyptus globulus Labill. clones planted across three different sites in Tasmania, Australia, were sampled for wood and kraft pulp/handsheet properties.• Site had a significant effect on all measured properties. Compared with the poor site (Parkham) the wood from the good site (West Ridgley) had on average 11% lower wood density. The poor site had also greater microfibril angles, shorter fibres at lower pulp yields.• The handsheets produced with pulp from the poor site result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
12
1
1
Order By: Relevance
“…This contrasts with findings of Wimmer et al (2008) who reported higher average MFA at slowgrowing compared to fast-growing E. globulus sites in Tasmania. In that study, the difference was probably a function of earlywood/latewood effects.…”
Section: Wood Properties In Slow and Fast Growing Treescontrasting
confidence: 56%
“…This contrasts with findings of Wimmer et al (2008) who reported higher average MFA at slowgrowing compared to fast-growing E. globulus sites in Tasmania. In that study, the difference was probably a function of earlywood/latewood effects.…”
Section: Wood Properties In Slow and Fast Growing Treescontrasting
confidence: 56%
“…Several studies have explored the effects of site and growth rate on wood properties in Australian plantation eucalypts (Raymond and Muneri 2001;Wimmer et al 2002Wimmer et al , 2008Downes et al 2006). For pulp production, the most important wood properties are basic density and KPY (Greaves et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…However, the wood and paper industries prefer black spruce to balsam fir because the former exhibits higher wood stiffness (Alteyrac et al, 2006). This parameter is directly linked to wood density, as well as microfiber angles (Cown, 2005;Downes et al, 2002;Wimmer et al, 2008). From an anatomical point of view, the major contributing factor to wood density is the proportion of latewood and, specifically, cell wall thickness (Antal and Micko, 1994;Ivkovich et al, 2002).…”
Section: Introductionmentioning
confidence: 99%